Eco-Friendly Energy Production: The Influence of Price Factors in the Regions of Russia - Roslyakova, Natalia; Vechkinzova, Elena (Frontiers in Energy Research, 2022)
Our review focuses on statistical data on the relationship between electricity prices and emissions, energy availability, and energy consumption in 2017–2020. We used the nonparametric method of data envelopment analysis (DEA) as a methodological basis for analyzing the impact of the "green policy" on electricity consumption in the regions of Russia and regression analysis to quantify dependencies between the parameter. The results of the DEA allowed us to check the effectiveness of the ratio of costs (emissions) and results (electricity consumption by the population and industry). The results of the regression analysis allowed us to find the equation of the relationship between the amount of electricity generated by a renewable energy source (RES), the amount of consumption, and average electricity prices. The obtained equations proved the strong influence of an increase in the amount of energy generated from renewable energy sources on the average electricity price increase and a decrease in energy consumption. In the conclusion, we talk about the low elasticity of the demand for electricity from the Russian population and the significant impact of electricity generated by the RES on increasing the average prices of energy producers and reducing energy consumption.